Employment of probability - based multi-response optimization in high voltage thermofluids - Ofodu, Joseph Chukwuka; Abifarin, Johnson Kehinde (Vojnotehnički glasnik / Military Technical Courier, 2022)
Introduction/purpose: Researchers of fluids for high voltage engineering application always experience problems when selecting and recommending specific fluids suitable for high voltage application. This is due to the dual functionality of fluids required for high voltage equipment.Methods: This study introduced and employed a probability-based multi-objective optimization technique in the selection of high voltage thermofluids. Beneficial and unbeneficial preferable probability utility indexes were employed based on the desired properties of oils.Results: It was shown that the nanofluid with 0.6 wt% Al2O3 is the most promising candidate for high voltage equipment compared to other produced fluids considered. It is also noteworthy to state that coconut oil exhibited better performance efficiency compared to standard oil. This study also identifies that the produced Jatropha oil was inadequate for high voltage equipment.Conclusion: In conclusion, a preliminary study essential for final usage of 0.6 wt% Al2O3 nanofluids and coconut oil for high voltage equipment is recommended as well as the improvement of the performance characteristics of Jatropha oil for  usage in high voltage equipment.
Keywords: preferable probability optimization; high voltage equipment; thermofluids; physicochemical properties; dielectric strength